2004
DOI: 10.1016/s0002-9440(10)63261-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell Tropism of Simian Immunodeficiency Virus in Culture Is Not Predictive of in Vivo Tropism or Pathogenesis

Abstract: SIVmac239/316 is a molecular clone derived from SIVmac239 that differs from the parental virus by nine amino acids in env. This virus, unlike the parental SIVmac239, is able to replicate well in alveolar macrophages in culture. We have not however, observed macrophage-associated inflammatory disease in any animal infected with SIVmac239/316. Therefore, we sought to examine the cell tropism of this virus in vivo in multiple tissues using in situ hybridization combined with immunohistochemistry and multilabel co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
0
37
1
Order By: Relevance
“…Analysis of tissues revealed that more than 95% of the infected cells remaining in these animals were macrophages (28). Furthermore, plasma viral loads of nearly 10 6 RNA copy eq/ml were sustained in the presence of a reverse transcriptase (RT) inhibitor to block new rounds of infection (28). The half-life of infected naive and resting memory CD4 ϩ T cells may also be considerably longer than that of activated CD4 ϩ T cells that support high levels of virus replication.…”
Section: Cd4mentioning
confidence: 95%
“…Analysis of tissues revealed that more than 95% of the infected cells remaining in these animals were macrophages (28). Furthermore, plasma viral loads of nearly 10 6 RNA copy eq/ml were sustained in the presence of a reverse transcriptase (RT) inhibitor to block new rounds of infection (28). The half-life of infected naive and resting memory CD4 ϩ T cells may also be considerably longer than that of activated CD4 ϩ T cells that support high levels of virus replication.…”
Section: Cd4mentioning
confidence: 95%
“…After deparaffinization in xylene, rehydration in phosphate-buffered saline, and antigen retrieval with steam (citrate buffer), sections were incubated with anti-sense SIV riboprobes (Lofstrand Labs Ltd) encompassing essentially the entire SIV genome as previously described. 13 SIVmRNA ϩ cells were detected by the 2-hydroxy-3-napthoic acid-2 phenylanalide phosphate (HNPP) Fluorescent Detection Set (Roche Diagnostics Corporation; red). Furthermore, SIV-infected cells detected by this technique were also colabeled using unconjugated primary antibodies for BrdU and CD3 (both from DakoCytomation), and then with secondary antibodies conjugated to either Alexa 488 or Alexa 633 (Molecular Probes).…”
Section: Phenotyping Siv-infected Cells In Tissues By In Situ Hybridimentioning
confidence: 99%
“…2) and macrophages were not clearly infected, both animals developed chronic immune activation, as reflected in BrdU incorporation in CD4 ϩ and CD8 ϩ T cells and HLA-DR expression on CD8 ϩ T cells. These animals also developed thrombocytopenia, which is commonly associated with SIV disease progression in pig-tailed macaques (108), and tissues at necropsy showed pulmonary arteriopathy uniquely associated with SIV infection (56)(57)(58). Singlegenome amplification of the Env cytoplasmic domain in both animals showed conservation of the ⌬GY mutation, as well as R751G, which is a well-described mutation for the SIVmac239 clone (65).…”
Section: Discussionmentioning
confidence: 88%
“…S1B in the supplemental material). At necropsy, both had evidence of SIV infection, including generalized lymphoid hyperplasia and thrombocytopenia, pulmonary arteriopathy, and thrombosis (56)(57)(58), despite only slight reductions in numbers and percentages of CD4 ϩ T cells in blood and gut lamina propria (see below). In contrast, SIVmac239-infected animals exhibited findings typical of simian AIDS, with one or more of the following: meningoencephalitis with multinucleated giant cells, severe anemia and thrombocytopenia, giant cell pneumonia, esophageal candidiasis, and intranuclear inclusion bodies consistent with cytomegalovirus infection.…”
Section: Viral Dynamics Of ⌬Gy Infection In Pig-tailed Macaquesmentioning
confidence: 99%